LOCAL KNOWLEDGE IN BABAD PANJALU MANUSCRIPT - Abdul Muin Muin; Yeni Wijayanti Wijayanti; Yadi Kusmayadi Kusmayadi (Universitas Sultan Ageng Tirtayasa, 2020)
The Babad Panjalu manuscript is a local cultural heritage that has not been uplifted and is widely known by the community, especially the Panjalu community, Babad Panjalu is one of the most useful sources of local knowledge today. This study aims to determine an overview of the contents of the manuscript and local knowledge contained in the Babad Panjalu text. This study used a historical method design with research steps, namely heuristics, criticism, interpretation, and the last stage, namely historiography, using a qualitative approach with data collection techniques, namely literature study or literature study. The results of this study indicate that Babad Panjalu is a copy manuscript which was completed on July 10, 1905, written by Prajadinata from Panjalu Ciamis. Babad Panjalu is a collection of C.M. Pleyte, which is stored in box 121 at the Jakarta National Library Museum, uses Sundanese as the medium and is written in the form of dangding or pupuh. Babad Panjalu reveals various local knowledge including knowledge about the world of fauna and flora, Sundanese musical instruments, Sundanese paribasa, sacred places in Panjalu, and the history of Panjalu.